De Javasche Bank Nationalization Policy: From Private Bank to Bank Indonesia, 1951-1953 - Fauzan Syahru Ramadhan; Desi Susanti; Khairana Zata Nugroho; Keke Pahlevi Daradjati (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This article examines the nationalization policy by the Indonesian government towards foreign private banks owned by the Dutch East Indies colonial government to become Bank Indonesia in the period of 1951-1953. De Javasche Bank was nationalized because having significant power in the economic, political and monetary sector, being a source of livelihood, and wealth. The article uses the historical method consisting of four stages, namely heuristics, criticism, interpretation and historiography. Throughout this research, the validity is obtained that on 30 April 1951, the Minister of Finance, Yusuf Wibisono, had plans to nationalize De Javasche Bank. On 2 July 1951, the Prime Minister Sukiman formed the De Javasche Bank Nationalization Committee. Sumitro Djojohadikusumo, the new Minister of Finance, submitted a draft law regarding the nationalization of De Javasche Bank on 22 August 1952 and it was approved on 10 April 1953 with the provisions of Law no. 11 of 1953.